Charge Transfer and Photocatalytic Activity in CuO/TiO2 Nanoparticle Heterojunctions Synthesised through a Rapid, One‐Pot, Microwave Solvothermal Route. Issue 11 (12th May 2015) - Moniz, Savio J. A.; Tang, Junwang
Abstract Rapid charge carrier recombination is a major limiting factor over efficiency in many semiconductor photocatalysts. To address this, copper(II) oxide/titanium dioxide (CuO/TiO2) heterojunctions were synthesised through a novel, rapid solvothermal microwave procedure using a low‐cost copper precursor and commercial P25 TiO2, taking as little as five minutes to synthesise well‐defined CuO nanoparticles onto the host TiO2, achieving an intimate contact. The resultant composites encompass pure CuO particles of approximately 6–7 nm diameter, confirmed by means of high resolution transmission electron microscopy and X‐ray photoelectron spectroscopy analysis. Photoelectrochemical water splitting was enhanced by nearly 2 times using the junction, whilst ≈1.6 times enhancement in the photocatalytic mineralisation of a model organic pollutant 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) was observed. Furthermore, we studied the initial decomposition mechanism of 2, 4‐D by means of GC‐MS analysis. The increase in catalytic activity, investigated by impedance analysis (Mott–Schottky plots) and photoluminescence spectra, is attributed to photoelectron transfer from the more negative conduction band (CB) of TiO2 to CuO, leaving the photohole on TiO2 to take part in oxidation reactions. This strategy allows for in situ charge separation which facilitates superior photocatalytic activity for both pollutant degradation and water splitting.